Methods Of Teaching Oral Communication In Short-Term Courses Of The Russian Language (Eurasian Journal of Learning and Academic Teaching, 2024)
In today's era of globalization, the importance of effective oral communication in a foreign language cannot be overstated. As the world becomes increasingly interconnected, the ability to communicate, negotiate and collaborate with people from different linguistic and cultural backgrounds has become a crucial skill. In the context of teaching Russian, teaching oral communication is especially important, given the complexity of the language and the cultural nuances that underpin it. Let's consider the methods of teaching oral communication in short-term courses of the Russian language, highlighting the most effective approaches, techniques and strategies that can be used to promote the development of this important skill in students.